(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This scientific work is dedicated to analyzing the development processes of small business entities and improving the efficiency of using digital technologies within them. The study examines the significance of small businesses in the economy, their key characteristics, and the advantages of implementing modern digital technologies. In particular, advanced practices of using artificial intelligence technologies and automating financial management processes have been explored. During the research, the economic indicators of small business entities were analyzed, and their strengths, weaknesses, opportunities, and threats were identified using the SWOT analysis method. Scientific and practical recommendations have been developed to enhance labor productivity, improve financial planning, and optimize management through the integration of digital technologies.